Mobile Phone Passive Positioning through the Detection of Uplink Signals for Search and Rescue - Yuhui Gao; Zhongliang Deng; Yao Zhang; Shihua Sun; Zhen Li (Sensors, 2019)
To satisfy the service requirements of high accuracy and efficient life detection and location for search and rescue (SAR) missions after a disaster, we developed a passive positioning method to locate mobile phones by capturing the random access preamble, which can be applied to fourth-generation (4G) and even fifth-generation (5G) communication systems. We analyzed the characteristics of the random access procedure of a communication system and established a way to detect mobile phones by combining the time-difference-of-arrival (TDOA) estimation to determine the location. Then, we performed an experiment and a simulation of preamble sequence acquisition, and the results proved that the method is feasible and has high detection accuracy in high-noise conditions.